Data for "Emotional demands and burnout: differential moderating effect of job resources and age" - Popucza, Timea Zsuzsanna (University of Gävle, 2025)
The dataset was generated within a research project in occupational health science focusing on emotional burdens in working life and their associations with health and well-being. The data material consists of survey data covering emotional demands, emotional labor (including the strategy of deep acting), burnout, and mental well-being, as well as potential protective work-related resources such as perceived meaning of work, job control, and social support. Background variables include occupation, age, and gender. Data were collected through web-based surveys distributed via social media and through employers. The dataset consists of a cleaned CSV file. Variables related to burnout have been recoded and reverse-coded in accordance with the applied burnout scale to ensure correct interpretation. No specialized software is required to access or use the data beyond standard programs capable of reading CSV files.

Datasetet har genererats inom ett forskningsprojekt i arbetshälsovetenskap med fokus på emotionella belastningar i arbetslivet och deras samband med hälsa och välbefinnande. Datamaterialet består av enkätdata som omfattar emotionella krav, emotionellt arbete (inklusive strategin deep acting), utbrändhet och psykiskt välbefinnande, samt potentiella skyddande resurser i arbetet såsom upplevd mening i arbetet, grad av kontroll och socialt stöd. Bakgrundsvariabler inkluderar bland annat yrke, ålder och kön. Data har samlats in genom webbaserade enkäter som distribuerats via sociala medier samt genom arbetsgivare. Datasetet består av en rensad CSV-fil. Variabler relaterade till utbrändhet har omkodats och reverserats i enlighet med den använda utbrändhetsskalan för att säkerställa korrekt tolkning av skalorna. Ingen särskild programvara krävs för att använda data utöver standardprogram som kan läsa CSV-filer.
Data för "Emotional demands and burnout: differential moderating effect of job resources and age"
Keywords: HEALTH; HÄLSA; PUBLIC HEALTH; FOLKHÄLSA; HEALTH PROFESSIONALS; HÄLSOPERSONAL; WELL-BEING (HEALTH); VÄLBEFINNANDE (HÄLSA); resources; resurser; burnout; utbrändhet; Emotional demands; Känslomässigt krav; General health and well-being; Allmän hälsa och välbefinnande; PSYCHOLOGY; PSYKOLOGI; Other Health Sciences; Annan hälsovetenskap; Psychology; Psykologi; Occupational health; Arbets- och miljömedicin; Public health; Folkhälsa